KEKUATAN MENGIKAT PUTUSAN AJUDIKASI OMBUDSMAN DALAM PROSES PENYELESAIAN SENGKETA PELAYANAN PUBLIK - Radjab, Abi Ma’ruf (Veritas et Justitia, 2015)
Based on the regulations as arranged in the Public Service Law, in case of legal disputes or lawsuits concerning public service, the settlement can be reached in two ways, namely by mediation and adjudication of a verdict, and secondly, this legal effort can be made or initiated by a so-called Ombudsman. The adjudication process subsequently yields a verdict or sentence that is bound to lead to contradiction as the Ombudsman is not a legal institution and this is not a quasi-administrative judicial process either, for the outcome of the Ombudsman’s investigation comes in the shape of a mere recommendation, and this cannot be regarded as a proper verdict pronounced by an official judge. Based on the regulations as stated in the Public Service Law and the Ombudsman Law as well as the regulations for their execution the adjucatory verdict reached by the Ombudsman, the force of this binding decision or sentence cannot be considered final and binding as such because it only qualifies as a recommendation. Given the fact that the judicial verdict made by the Ombudsman in the settlement of lawsuits regarding Public Service comes in the shape of a recommendation, further legal efforts can be made in accordance with the existing regulations whose mechanism is similar to that of administrative appeals that culminate in imposing sanctions and publication in the media to expose the case in question.